2023
DOI: 10.1101/2023.02.23.529672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angiopoietin-like 4 promotes the proliferation and migration of epidermal stem cells and contributes to the re-epithelialization of cutaneous wounds

Abstract: Proliferation and migration of epidermal stem cells (EpSCs) are essential for epithelialization during skin wound healing. Angiopoietin-like 4 (ANGPTL4) has been reported to play an important role in wound healing, but the mechanisms involved are not fully understood. Here we investigate the contribution of ANGPTL4 to full-thickness wound re-epithelialization and the underlying mechanisms using Angptl4 knockout mice. Immunohistochemical staining reveals that ANGPTL4 is significantly upregulated in the basal la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The collagen type ratio of 30 laser group on the 7th and the 14th day was between 2 and 2.5, which on the one hand ensured the healing speed and softness of tissue to a certain extent, but also indicated that the proliferation process of COL-1 fibers was much slower. Although the wounds of the samples were completely closed on day 14, the proliferation of COL-1 fibers in the later stage would take a longer time [38,[56][57][58].…”
Section: Collagen Distribution During Wound Healingmentioning
confidence: 99%
“…The collagen type ratio of 30 laser group on the 7th and the 14th day was between 2 and 2.5, which on the one hand ensured the healing speed and softness of tissue to a certain extent, but also indicated that the proliferation process of COL-1 fibers was much slower. Although the wounds of the samples were completely closed on day 14, the proliferation of COL-1 fibers in the later stage would take a longer time [38,[56][57][58].…”
Section: Collagen Distribution During Wound Healingmentioning
confidence: 99%